PENGARUH PENGGUNAAN MEDIA PAPAN FLANEL KATA (FLANKAT) TERHADAP PENINGKATAN PENGUASAAN KOSAKATA SISWA SMALB-B - Utami Nur Karimah; Endro Wahyuno (Universitas Negeri Malang, 2014)
The purposes of this research were to describe vocabulary mastery of students grade X SMALB-B YPTB before and after using a word flanel board media (flankat) and to determine the effect of word flanel board media (flankat) to increase the vocabulary mastery of hearing impairment students grade X SMALB-B YPTB Malang. This research was a quantitative research and used quasi experiment with time series design. The data collection was from the test result. Two types of data were the results of pre-test (before given the treatment) and post-test (after given the treatment). The results of the data analysis was found that the average scores of students at the time of the pre-test was 39, while on the post-test was 85.5. The result of output value asymp sig. (2-tailed) was 0, 028. It can be concluded that the usage of the word flanel board media (flankat) had influence toward the improvement of vocabulary mastery for students grade X SMALB-B. Tujuan dari penelitian ini adalah untuk menggambarkan penguasaan kosakata siswa SMALB-B sebelum dan setelah menggunakan media papan flanel kata (flankat) dan untuk mengetahui pengaruh flankat untuk meningkatkan kosakata pendengaran siswa penurunan SMALB-B. Penelitian ini merupakan penelitian kuantitatif dan menggunakan eksperimen semu dengan desain time series. Pengumpulan data diperoleh dari hasil uji pre-test (sebelum diberi perlakuan) dan post-test (setelah diberi perlakuan). Hasil analisis data ditemukan bahwa nilai rata-rata pre-test adalah 39, dan post-test adalah 85,5. Hasil nilai output asymp sig. (2-tailed) adalah 0, 028 dan asymp sig. (2-tailed) <α. Jadi dapat disimpulkan bahwa penggunaan media papan flanel kata (flankat) memiliki pengaruh terhadap peningkatan penguasaan kosakata untuk siswa SMALB-B